Numerical Simulation of Flow Boiling in Small Channel of Plate OTSG - Yuan, Xiaofei; Yang, Lixin; Tian, Zihao; Han, Shuang; Lu, Hongyan (Frontiers in Energy Research, 2020)
The plate OTSG (once-through steam generator) with channel diameter of 1-3 mm has high volume-power ratio and powerful resistance to high temperature and high pressure. It can well satisfy the needs of integrated development of nuclear power pressure vessel. The heat transfer characteristics of flow boiling in the channel have aroused increasing concerns from scholars in this field. Based on the experimental results achieved by the researcher in our team, the drift flux model is applied to simulate the flow boiling heat transfer coefficients in the rectangular channel with hydraulic diameter of 1.7 mm. The drift velocities and the distribution parameter are obtained by the empirical correlations of the horizontal flow. The simulation software is STAR-CCM+, and the simulation boundary conditions comply to the experimental conditions. The simulation results indicate that the growth trends of the heat transfer coefficients along the path are consistent with the growth trends of the experimental results. The drift velocities and the distribution parameters have little effect on the heat transfer coefficients of the horizontal small channel. When the drift velocity is 0, compare with the experimental data, the heat transfer coefficients in the early stage of the flow under high pressure are well higher, while those in the late stage of the flow increase, even though they are still lower. The error between the predicted and the experimental is from - 50% to + 50%. Similarly, the simulation values of boiling heat transfer coefficients under low pressure are generally lower than experimental values. And the error between the predicted and the experimental is from - 60% to + 10%.